A comprehensive numerical study exploring the significance of thermally reactive bioconvection in Falkner-Skan flow of Williamson nanomaterials influenced by activation energy and buoyancy forces - M. Israr Ur Rehman; Haibo Chen; Aamir Hamid; Wu Qian; Refka Ghodhbani; Mohamed Hussien (Case Studies in Thermal Engineering)
Heat and mass transport performance is greatly improved in a variety of industrial, engineering, and technological applications by the advanced thermal properties of nanomaterials, which are enhanced by chemical reactions, nonlinear thermal radiation, nonuniform heat sources/sinks, Arrhenius kinetic energy, and induced electromagnetic forces. The analysis is further improved by adding thermophoretic diffusion and Brownian motion to the energy and concentration equations Bio-fuels, enzymes, industry, bio-sensors, petroleum, and a number of other novel biotechnological features are also influenced by the bioconvective mechanisms in nanomaterials. Motivated by these properties, this study investigates the rheological behavior of non-Darcian Williamson nanomaterials interacting with motile microorganisms, driven by Falkner-Skan wedge surfaces. Similarity transformations are used to convert the system of partial differential equations into a system of ordinary differential equations, which are then numerically solved using the Runge–Kutta–Fehlberg (RKF-45) method. After the system has been altered, the physical parameters that result are examined and shown graphically. The raising valuation of wedge angle parameter diminished the velocity and friction drag. Moreover, higher thermal radiation and electric parameter also escalate the thermal field. Nanoparticle concentration is improving function via Arrhenius activation energy.